2017
DOI: 10.3138/ptc.2015-77
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Using a Remote Presence Robot to Improve Access to Physical Therapy for People with Chronic Back Disorders in an Underserved Community

Abstract: Purpose: The purpose of this case study was to evaluate the delivery of an inter-professional (IP) spinal triage management approach to chronic back disorders using remote presence robotic technology as an innovative form of telerehabilitation in a northern Saskatchewan community. Methods: The IP team, consisting of a local nurse practitioner (NP) and a physical therapist in an urban centre, completed a comprehensive neuromusculoskeletal assessment of, and one follow-up visit with, a post-surgical spinal patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The health providers in the present study described the mutual professional benefit, in terms of capacity building on the rural team, as well as enhanced practice due to the interprofessional team. This was also identified by practitioners who utilized remote presence robotics (another form of telehealth) to address a CBD case in remote northern Canada 21…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The health providers in the present study described the mutual professional benefit, in terms of capacity building on the rural team, as well as enhanced practice due to the interprofessional team. This was also identified by practitioners who utilized remote presence robotics (another form of telehealth) to address a CBD case in remote northern Canada 21…”
Section: Discussionmentioning
confidence: 99%
“…Effective interprofessional practice was a primary theme identified in our study. The present study builds on the N of 1 study by Lovo Grona et al21 with a larger sample, different technology, and a different rural community location. The CIHC identified six competency domains of interprofessional practice: interprofessional communication, patient/client/family/community-centered care, role clarification, team functioning, collaborative leadership and interprofessional conflict resolution 22…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown to be a valid and reliable intervention for musculoskeletal physical therapy conditions ( Lee et al, 2018 ). Intervention studies comparing in-person to telerehabilitation physical therapy demonstrated similar improvements in health outcomes including pain and function ( Lovo Grona et al, 2016 ). In physical therapy for developmental disorders, telerehabilitation has been used as an alternative to in-person treatment with success ( Olson et al, 2018 ).…”
mentioning
confidence: 99%